Forecasting Trends in Invasive Pneumococcal Disease among Elderly Adults in Quebec. (26th January 2017) - Zhou, Z.; Deceuninck, G.; Lefebvre, B.; De Wals, P.
Abstract : Background. In Canada, the current recommendation is to offer PPV23 to adults ≥ 65 years. PCV13 is now licensed for adults. Methods. Invasive pneumococcal disease (IPD) cases in adults 65–74 years of age in the Quebec notifiable diseases registry were classified into five serotype categories. Poisson regression models were fitted to monthly rates observed in 2000–2014 and predictions were made for 2015–2024, using theoretical assumptions regarding indirect effects of childhood vaccination and serotype replacement. Results. IPD rates caused by PCV7 serotypes decreased markedly since PCV7 introduction for children in December 2004. This trend is also underway for additional PCV13 serotypes except serotype 3. Additional PPV23 serotypes and nonvaccine serotypes have been on rise since 2004 and this is expected to continue. A small decrease in overall IPD incidence in the next decade is predicted. The proportion of PCV13 serotypes represented 33% of IPD cases in 2014 and would be 20% (95% CI: 15% to 28%) in 2024. PPV23 coverage was 53% in 2014 and is expected to be 47% (95% CI: 26% to 85%) in 2024. Conclusion. The potential usefulness of a combined PCV13 + PPV23 program for elderly adults would decrease over time but PCV13 would be the only option to prevent serotype 3 IPD.